Carte d'AmeÌrique dresseÌe pour l'usage du roy en 1722. - L'Isle, Guillaume de, 1675-1726 (Ph. Buache son Gendre, 1763)
Map shows major settlements, areas of Indian habitation, physical features, and political divisions for North and South America, including French Louisiana and New Spain; Mediterranean Sea, southern tip of Great Britain and Ireland, and western coast of Europe and Africa; large "Mer de l'Ouest [western sea] shown north of California. Includes notes and discovery dates, title courtouche and "Advertissement." Inset: [Map of] "Mer Glaciale et Terres Arctiques." Relief shown pictorially. Scale not given.